2012
DOI: 10.1038/labinvest.2012.7
|View full text |Cite
|
Sign up to set email alerts
|

Assaying macrophage activity in a murine model of inflammatory bowel disease using fluorine-19 MRI

Abstract: Macrophages have an important role in the pathogenesis of most chronic inflammatory diseases. A means of non-invasively quantifying macrophage migration would contribute significantly towards our understanding of chronic inflammatory processes and aid the evaluation of novel therapeutic strategies. We describe the use of a perfluorocarbon tracer reagent and in vivo 19F magnetic resonance imaging (MRI) to quantify macrophage burden longitudinally. We apply these methods to evaluate the severity and three-dimens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
71
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(75 citation statements)
references
References 50 publications
4
71
0
Order By: Relevance
“…In this respect, in a previous study, it has already been shown that perfluorocarbon particles can be used to track macrophages using MRI in a murine colitis model. 52 Similarly, a number of studies have proven that ultrasmall paramagnetic iron oxide particles may be useful to track macrophages in a number of animal models [53][54][55] and may be therefore also used to better investigate the immunological response in the DSS model.…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, in a previous study, it has already been shown that perfluorocarbon particles can be used to track macrophages using MRI in a murine colitis model. 52 Similarly, a number of studies have proven that ultrasmall paramagnetic iron oxide particles may be useful to track macrophages in a number of animal models [53][54][55] and may be therefore also used to better investigate the immunological response in the DSS model.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the vast majority of studies that perform cell tracking with 19 F MRI have employed spin echo sequences. [16][17][18][19][37][38][39][40] Using the 3D bSSFP sequence, we injected and detected 1.5×10 6 Cell Sense-labeled hMSC in vivo on day 0 using a spatial resolution of 2 mm 3 (2 µL). If we assume that on day 0 all of the injected cells are present and evenly distributed, then we detected 30,000 cells per voxel.…”
Section: Cell Detection With Bssfpmentioning
confidence: 99%
“…PFC nanoemulsions have been applied in in situ labeling of macrophages and visualizing their accumulation in diseases such as arthritis [10], inflammatory bowel disease [16], cancer [17], neuroinflammation [18], and pulmonary inflammation [19]. Our lab and others have also reported dual mode nanoemulsions that incorporate fluorescent dyes and PFCs for macrophage imaging [17, 18, 20, 21] and also on the in vitro utility of nanoemulsions with therapeutic capabilities [21].…”
Section: Introductionmentioning
confidence: 99%